Investigating Green Marketing Orientation Practices among Green Small and Medium Enterprises - Rajadurai J.; Zahari A.R.; Esa E.; Bathmanathan V.; Ishak N.A.M. (Korea Distribution Science Association (KODISA), 2023)
This study aims to establish the relationship between the Green Marketing Orientation (GMO) variables and the performance of Green Small and Medium Enterprises (GSMEs) across the building and energy sectors in Malaysia, using customer satisfaction as a means of performance measurement. The GMO variables examined include Greening the Process (GTP), Green Supply Chain Management (GSCM), Green Strategic Policy Initiatives (GSPI), Proactive Energy Conservation (PEC) and Green Promotion (GP). The items used to measure these variables were extracted from literature and adapted to the context of the variables based on feedback from Focus Group Discussions and Expert Opinion sessions. This study employs a survey sample of 300 respondents but only 238 completed questionnaires were returned. The results reveal that GTP, GSCM and PEC have a positive impact on Customer Satisfaction but not GSPI and GP. The findings suggest that owners or managers of GSMEs should focus on maintaining and improving GTP, GSCM and PEC in order to create greater satisfaction among their customers. The significance of this study is that it enables the creation of a framework that enables GSMEs to design a pathway towards achieving a cleaner production of goods and services in line with United Nations Sustainable Development Goals. 2021. This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (https://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. All rights reserved.